PERAN SERVANT LEADERSHIP DAN EMPLOYEE ENGAGEMENT DALAM MENINGKATKAN KINERJA INOVASI PADA UKM KRIYA DI PROVINSI BALI - Ni Putu Kusuma Widanti; Ida Ayu Agung Paramitaswari; Ni Kadek Pajar Kusumawati; Adisti Maharani Krisna; Ni Wayan Septiawini (Journal Research of Management, 2026)
Innovation performance is a critical factor in enhancing business competitiveness and long-term sustainability, particularly for craft Small and Medium Enterprises (SMEs) operating in an increasingly dynamic business environment. This study aimed to examine the effects of servant leadership and employee engagement on innovation performance among craft SMEs in Bali Province, Indonesia. A quantitative research design was employed using a survey of 86 craft SMEs selected through simple random sampling. The collected data were analyzed using multiple linear regression analysis. The findings revealed that servant leadership had a positive and significant effect on innovation performance. Likewise, employee engagement exerted a positive and significant influence on innovation performance. The model produced an Adjusted R² of 0.620, indicating that servant leadership and employee engagement explained 62% of the variance in innovation performance, while the remaining 38% was explained by other factors outside the proposed model. These findings support Social Exchange Theory, suggesting that leaders who prioritize serving, empowering, and supporting employees foster reciprocal relationships that strengthen employee engagement and ultimately enhance innovation performance. The study provides practical implications for craft SME owners by emphasizing the importance of implementing servant leadership practices and fostering employee engagement to improve innovation performance and sustain business competitiveness.